Using the chloroplast rbcL gene to clarify the relationship between species of the genus Stephania (Menispermaceae) from Vietnam - Chinh, Vu Tien; Lieu, Tran Thi; Tang, Duong Van (Academia Journal of Biology, 2020)
The rbcL gene of the chloroplast genome is widely used as an additional data for the study of species origin, molecular evolution and phylogeny. In this study, we used the rbcL gene to separate three species of genus Stephania: S. japonica, S. polygona, S. rotunda and one subspecies S. japonica var. discolor from Vietnam. Molecular analysis was performed on 523 bp segment of the rbcL genes with 4 examined samples of the genus Stephania and 18 other genbank sequences of five genera Pachygone, Antizoma, Cissampelos, Cyclea and Syntriandrium. The dataset consists of 22 sequences used to reconstruct the evolutionary tree using two methods: Bayesian Infer (BI) and Maximum Likelihood (MP). The results showed that S. rotunda was able to distinguish from S. japonica or S. polygona, while S. japonica, S. japonica var. discolor and S. polygona could not distinguished each another. The phylogenetic tree splited three examined species into two groups, representing the two main groups of morphology in genus Stephania: a group with tuberous rootstock and another group with main root.